2021
DOI: 10.1080/23802359.2021.1884029
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome of Amphinemura bulla Shimizu, 1997 (Plecoptera: Nemouridae) from Japan

Abstract: The genus Amphinemura belongs to the family Nemouridae (Plecoptera) and has 205 species in the Holarctic and Oriental Regions. We sequenced the fourth complete mitochondrial genome of A. bulla Shimizu, 1997. The mitogenome is 15,827 bp long with 37 genes plus a control region with an A þ T content of 68.9%. There are 10 intergenic spacers (75 bp total) and 13 gene overlaps (43 bp total). All protein-coding genes (PCGs) use normal initiation codons, except ND1 and ND5 which begin with TTG and GTG. Two PCGs (COI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
1
6
1
Order By: Relevance
“…Similarly, the high A + T content value among the 3 partitions also occurs in the partial mitogenome of L. tumana ( Table 2 ). As with published stoneflies ( Chen and Du 2017a , 2017b , Wang et al 2017 , 2021 , Cao et al 2019 , 2021 , Chen et al 2020 , Zhao et al 2020 , Guo et al 2022 ) and other insects ( Wei et al 2010a ), all 3 species showed a positive AT-skew and negative GC-skew in the whole mitogenome ( Table 2 ).…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Similarly, the high A + T content value among the 3 partitions also occurs in the partial mitogenome of L. tumana ( Table 2 ). As with published stoneflies ( Chen and Du 2017a , 2017b , Wang et al 2017 , 2021 , Cao et al 2019 , 2021 , Chen et al 2020 , Zhao et al 2020 , Guo et al 2022 ) and other insects ( Wei et al 2010a ), all 3 species showed a positive AT-skew and negative GC-skew in the whole mitogenome ( Table 2 ).…”
Section: Resultssupporting
confidence: 72%
“…Differences in gene length among 3 Nemourinae species were primarily caused by insertions/deletions in the intergenic spacers and control region ( Supplementary Tables S1 – S3 ). The gene order of 3 Nemourinae mitogenomes is the same as all previously published stonefly mitogenomes 22–30 ( Chen and Du 2017a , 2017b , Wang et al 2017 , 2021 , Cao et al 2019 , 2021 , Chen et al 2020 , Zhao et al 2020 , Guo et al 2022 ), as well as the ancestral gene order of Drosophila yakuba ( Clary and Wolstenholme 1985 ).…”
Section: Resultsmentioning
confidence: 80%
“…The genus Amphinemura that belongs to Amphinemurinae was sister to Nemoura of the subfamily Nemourinae (PP = 94, BP = 1.00). The sister relationship between Amphinemura and Nemoura is not consistent with the traditional classification [53] but consistent with some mitogenome analyses [8,54]. Considering that only one genera data of Nemourinae is available, more sampling from different genera of this subfamily is needed to test this problem.…”
Section: Phylogenetic Analysismentioning
confidence: 68%
“…Eleven PCGs had TAN (TAA or TAG) as their last codon; however, cox1 and nad5 both had shortened termination codons and concluded with T (Table S1). The use of incomplete stop codon T is mutual in most of the stoneflies [20,23,27,28,40,57] and other animals' mitogenome [5], forming a comprehensive TAA terminal signal via post-transcriptional polyadenylation [58,59].…”
Section: Protein Coding Genesmentioning
confidence: 99%